Aesthetic transformation of short plays presented to children (Journal of the College of Basic Education, 2023)
The overlap between the text and the show opened a wide horizon in understanding the relationship between them and which is more important and lasting, so what is the relationship between the play and the theatre, and what are the components of the text that is suitable for the show? Accordingly, the research was divided into two axes: The first axis: I consider that the abundance of literary production has led to a diminishing of theatrical performances, and has made room wide for reading and reading. these texts, or most of them, to the tree, in the presence of Some theatrical performances that continue to be shown for months, or even for consecutive years, have outweighed the interest of reading at the expense of the show. As for the second axis: starting from the dichotomy of text and presentation in short plays, it is represented in considering the play as a text written in order to be presented, and this is a vision adopted by a number of writers and directors, and this view revolves around linking it to the stage of the theater. It is true that the original in the play is that it is a work made for show and not For reading only.Therefore, if many of the short theatrical texts in Western and Arab literature entered the curricula of study and were read as good literature, and were printed in books and republished many times, the original in theater remains constant. In that the text was written not only to be read, but to be presented on stage Thus, all these elements overlap with each other to contribute to the glow of the text and the illumination of the dark sides in it, which is what the literary reading of the text cannot achieve in order to embody the features of the richness and glow of this text. And maybe the director did A different vision, such as transforming the text from one intellectual state to another suggested by the director through his reading of this text. Because the different visions between the directors, the different ways of dealing with the play, and the multiplicity of cultures are basic factors that stand behind the multiple output of a single text. . I made it a theatrical performance in the first place. The text’s artistic, literary and functional importance is not evident except through its embodiment in a visible and tangible act, that it reaches others through the eye, the ear, and the general feeling that is related to the prevailing life. comprehensive cultural and social life.The research in the second chapter included two topics: The first topic: the short theatrical textThe second topic: the short theatrical showThe second chapter came out with a set of indicators, including:1/ Children’s theater can contribute to the upbringing of children, providing them with a lot of knowledge and concepts, making them aware of social relationships and roles, knowing their rights and duties towards themselves and their country, improving their personality, training them on positive behaviors that work on their integration into society, knowing their society’s issues and how to provide solutions to them, so that the child becomes a successful individual. and interacting within the community2/ Children's theater is a comprehensive theatre, capable of presenting scientific material to the child in a simple and interesting manner, and is also able to instill sound moral and social values in the hearts of children, and urge them to virtues.In the third chapter, the performance of the play The Returning Stranger was analyzed as a sample for the researchThe research came out with a number of results, including1/ The aesthetic transformation of the discourse of the short play (The Returning Stranger), is based on a basic dichotomy (text, presentation) as an integral and indivisible dichotomy, and one cannot be separated from the other or done without the other within the theatrical show arts that are based on art, performance and expression. 2/ The presentation of the play The Returning Stranger is an achievement that was completed by the availability of a set of contradictory and discordant systems, signs, and evidence. This means that this short theatrical text is a creative writing materially embodied in a theatrical performance that the child was able to deal with better than how he deals with other literary genres. The research also reached a set of conclusions, including:1/ The short play is the most suitable for expressing children’s issues, and it is the most suitable for those who direct children’s plays according to their age stages.2/ The experimental space of the short plays is not limited to the language and the voice of the actor, but rather goes beyond it to include all visual and sound effects. Music, for example, in theatrical performance occupies an important space in the world of signs, symbols and interpretations.